“The people’s fish”: Sociocultural dimensions of recreational fishing for Atlantic mackerel in Nova Scotia - Hamelin, Kayla M.; MacNeil, M. Aaron; Curran, Kaitlyn; Bailey, Megan (Frontiers in Marine Science, 2022)
Atlantic mackerel or Amalamaq (Scomber scombrus) has been subject to diverse fishing pressures in Atlantic Canada for commercial, bait, recreational, and Indigenous food-social-ceremonial (FSC) fisheries, resulting in its substantial social and cultural significance in the region. Recent stock declines have led to closures of the commercial and bait mackerel fisheries, while recreational and FSC harvesters retain respectively the ability or right to fish. Here we assess the human dimensions of the recreational mackerel fishery through administration of a voluntary questionnaire shared at wharfs and through online/social media channels. A total of 285 responses were received, with results providing a rich picture of this poorly-engaged stakeholder community. The operational dimensions of this fishery and benefits derived from recreational fishing are explored. While recommendations for conservation and management measures were not solicited explicitly, many respondents shared comments and suggestions regarding management of the stock. Engaging more actively with recreational mackerel anglers may allow for enhanced assessments of the fishery and foster local stewardship toward more effective fisheries management.